VECTORS OF DEVELOPMENT OF UKRAINIAN AGRICULTURE - HUZENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the current state and key development trends in Ukrainian agriculture under modern conditions, with particular emphasis on the impact of wartime challenges. The study highlights the significant transformations occurring in the agricultural sector, focusing on both structural and economic shifts. A detailed examination is conducted on the dynamics of the number of agricultural enterprises, especially those specializing in organic production, which is recognized as a vital and rapidly growing segment of the national agri-food market. The article underscores the crucial role agriculture plays in shaping Ukraine’s Gross Domestic Product (GDP), offering insights into the sector’s broader economic influence amid geopolitical instability.Changes in the structure of cultivated areas are explored in depth, revealing patterns of regional variation and identifying trends in either the expansion or contraction of agricultural land use. The analysis also addresses the implications of these changes for production efficiency and sustainability. Furthermore, the article evaluates Ukraine’s agricultural export potential in light of disrupted logistics, shifting international demand, and the necessity to reorient supply chains. Special attention is given to the strategic importance of diversifying export destinations and enhancing the resilience of agricultural exports.To navigate the new economic landscape, the author proposes a range of adaptation strategies, including the adoption of innovative technologies, increased government support, and the attraction of both domestic and foreign investment. The expansion of both internal and international markets for Ukrainian agricultural products is positioned as a critical step towards economic recovery and sustainable development. Finally, the promotion of organic farming is presented not only as a response to European market demands but also as a means of ensuring national food security and promoting environmentally responsible agricultural practices. This orientation aligns Ukrainian agriculture with contemporary European standards and offers a promising path for sectoral modernization.
Keywords: agriculture; agricultural sector; agricultural economy; organic production; sown areas